A Book Critique - Public Transportation Systems by Dr. Alexandros K. Chatzidouros - Vlastos, Thanos (SPOUDAI Journal of Economics and Business, 2012)
A Book Critique by Prof. Thanos Vlastos, for the Book "Public Transportation" written by Dr. Alexandros K. Chatzidouros and Published by“Patakis” Publications (ISBN 978-960-16-4125-6).